Removal of phthalic acid dieters with dissolved organic matter by an anaerobic/anoxic/oxic leachate treatment process. Issue 66 (27th November 2019) - Fang, Chengran; Mao, Hongzhi; Long, Yuyang
Abstract : The removal of di- n -butyl phthalate (DBP) and di(2-ethylhexyl) phthalate (DEHP) with dissolved organic matter (DOM) was studied in a laboratory scale anaerobic/anoxic/oxic reactor for landfill leachate treatment. Abstract : The removal of di- n -butyl phthalate (DBP) and di(2-ethylhexyl) phthalate (DEHP) with dissolved organic matter (DOM) was studied in a laboratory scale anaerobic/anoxic/oxic reactor for landfill leachate treatment. The removal rate was up to 98.0% for DBP and 78.2% for DEHP, which was related to humification of DOM ( i.e., the aromaticity and molecular weight (MW) of humic substances in landfill leachate). The dissolved organic carbon (DOC) was mostly humic acid and fulvic acid in the fraction of 1–100 kDa MW, indicating strong aromaticity and a high DBP/DEHP concentration. With complete removal of the fraction, the removal rate of DBP/DEHP was also high. The positive correlation of the DOC and DBP/DEHP concentration in raw leachate and the effluent from each reactor showed that the interaction between DOM and DBP/DEHP facilitated the removal of organic pollutants.